Achieving COVID‐19 herd immunity in Rwanda, Africa - Theogene Uwizeyimana; Emery Manirambona; Shuaibu Saidu Musa; Emmanuel Uwiringiyimana; Darius Bazimya; Kedest Mathewos (Wiley, 2023)
Abstract The COVID‐19 pandemic has caused significant disruption to global healthcare systems, including Rwanda's. Rwanda has taken measured actions in response to the pandemic using a multisectoral and one‐government approach. The introduction of the COVID‐19 vaccine boosted the hope of many people but has left debates on the measure of the population required to attain herd immunity. Herd immunity threshold (HIT) was introduced to track progress toward containing COVID‐19. HIT represents the number of people with long‐term immunity from COVID‐19. World Health Organization (WHO) established population vaccination targets for all countries worldwide, which included 40% coverage of the entire population by the end of 2021 and 70% by June 2022. In this paper, we discussed the efforts and progress that have been made so far toward achieving herd immunity in Rwanda.